Otimização da operação diária de usinas hidrelétricas em cascata utilizando metaheurísticas - Gomes, Carlos Augusto Machado (2018)
This work presents the development of an optimization model for the daily scheduling operation of cascade hydropower plants using metaheuristics. The scheduling of the day-to-day operation of hydropower plants aims at defining the unit commitment and the generation levels in order to meet a generation pattern established by the other planning stages, reducing the amount of water used. The hydroelectric system was considered with individual representation of generating units, machines’ efficiency curves and operation of reservoirs. The objective of the problem is to define an optimal operation, defining the dispatch at machine levels. It is an integer-mixed optimization problem, with real and binary variables. The solution proposed to the problem was through metaheuristic methods, whose characteristic allows solving the problem generically, applicable to any similar system, allowing the replication of the solutions presented in other similar optimization scenarios.